Advanced Engine Technologies for Turbochargers Solutions - Rareș-Lucian Chiriac; Anghel Chiru; Răzvan Gabriel Boboc; Ulf Kurella (Applied Sciences, 2021)
Research in the process of internal combustion engines shows that their efficiency can be increased through several technical and functional solutions. One of these is turbocharging. For certain engine operating modes, the available energy of the turbine can also be used to drive an electricity generator. The purpose of this paper is to highlight the possibilities and limitations of this solution. For this purpose, several investigations were carried out in the virtual environment with the AMESim program, as well as experimental research on a diesel engine for automobiles and on a stand for testing turbochargers (Turbo Test Pro produced by CIMAT). The article also includes a comparative study between the power and torque of the naturally aspirated internal combustion engine and equipped with a hybrid turbocharger. The results showed that the turbocharger has a very high operating potential and can be coupled with a generator without decreasing the efficiency of the turbocharger or the internal combustion engine. The main result was the generation of electrical power of 115 W at a turbocharger shaft speed of 140,000–160,000 rpm with an electric generator shaft speed of 14,000–16,000 rpm. There are many constructive solutions for electrical turbochargers with the generator positioned between the compressor and the turbine wheel. This paper is presenting a solution of a hybrid turbocharger with the generator positioned and coupled with the compressor wheel on the exterior side.